2011
DOI: 10.1097/cej.0b013e3283429e77
|View full text |Cite
|
Sign up to set email alerts
|

Is cardia cancer aetiologically different from distal stomach cancer?

Abstract: The coexistence of two aetiologically distinct types of cardia cancer, with distinctive histological characteristics of the neoplastic and nonneoplastic gastric mucosa, may explain the heterogeneous evidence of its association with Helicobacter pylori infection. We compared gastric cardia and noncardia cancers with regard to the frequency of H. pylori infection, the histological characteristics of the nonneoplastic gastric mucosa and the tumour histological type. We evaluated 41 cardia and 339 noncardia cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
2
7
0
1
Order By: Relevance
“…Overall long-term survival was comparable among GCA and non-cardia patients; however, we did note that early stage patients with GCA had a worse 5-year OS and DFS. Some studies have suggested that GCA may be more biologically aggressive with increased lymphatic and serosal invasion [11][12][13][14]. In the present study, we noted that some clinicopathological features between GCA and non-cardia patients were similar while others were different (Table I).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Overall long-term survival was comparable among GCA and non-cardia patients; however, we did note that early stage patients with GCA had a worse 5-year OS and DFS. Some studies have suggested that GCA may be more biologically aggressive with increased lymphatic and serosal invasion [11][12][13][14]. In the present study, we noted that some clinicopathological features between GCA and non-cardia patients were similar while others were different (Table I).…”
Section: Discussionsupporting
confidence: 64%
“…Some studies have suggested that GCA may be more biologically aggressive with increased lymphatic and serosal invasion . In the present study, we noted that some clinicopathological features between GCA and non‐cardia patients were similar while others were different (Table ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Published articles were included when all of the following criteria were met: (1) original reports of case-control or cross-sectional studies, including baseline evaluations of randomized clinical trials or cohort studies; (2) articles addressing the association between tobacco smoking and the occurrence of IM in human adults; (3) exposure defined as smoking cigarettes, pipes, bidis or cigars; and (4) outcome defined as intestinal metaplasia of the stomach, excluding the cardia, as this is a more heterogeneous condition that may follow the aetiology of oesophageal more closely than that of gastric cancer [18][19][20]. Among reports with overlapping samples, we selected those providing data regarding the largest number of cases or presenting more detailed information regarding tobacco exposure.…”
Section: Selection Of the Studiesmentioning
confidence: 99%
“…Gastric cancer can generally be classified into two categories: cardia gastric cancer (CGC) arising in the area of the stomach adjoining the esophageal-gastric junction, and non-CGC (NCGC) arising from more distal regions of the stomach. Several investigators have suggested that cardia gastric cancer may have distinct risk factors, clinical features and biological behavior compared with non-CGC [22, 27, 28]. Risk factors for CGC include obesity, GORD and Barrett's esophagus, a metaplastic condition that can result from GORD [8, 9, 29, 30]].…”
Section: Discussionmentioning
confidence: 99%